PELATIHAN PELATIH FISIK TINGKAT DASAR UNTUK SEMUA CABANG OLAHRAGA - Tirtawirya, Devi; FX Sugiyanto; Aryanto, Budi; Supriyanto, Agus (Universitas PGRI Yogyakarta, 2025)
Sports events both in the region and nationally are a place to search for talents and show their abilities in terms of sports achievements. The results of the championships in the area are capital for higher coaching, for example National Training (Pelatnas). Many club or regional coaches lack an understanding of the physical condition of athletes. This is what causes the gap in knowledge level. Because we know that physical condition is the most important component in supporting athletes' achievements. The lack of understanding related to physical conditions is due to the fact that in the regions there is still a very minimal increase in human resources, especially physical coaches in sports. If left unchecked, it is feared that it will reduce the performance of athletes. The implementation method for improving the human resources of physical trainers is to conduct a national-level physical trainer training that last for four days. This training is attended by coaches from various sports branches from different regions. The training process is carried out theoretically and through practical field application. Based on the result of the training activities and the assessments conducted to determine of the training materials, it has been found that 5.6% of the participants have not yet met the assessment standards, while 94.4% of the the participants have understood the standard level of material comprehension. Keywords: Coach, Strength and conditioning, Sports